Renal function in liver recipients: in-depth analysis of data from the Local Scientific Transplant Registry of the Burnasyan Federal Medical Biophysical Center - A. I. Sushkov; V. S. Rudakov; M. V. Popov; A. E. Kalachyan; E. V. Naydenov; A. I. Artemiev; S. E. Voskanyan (Трансплантология (Москва), 2025)
Background. Renal dysfunction is common in liver transplant candidates and recipients. However, despite more than 30 years of experience with liver transplantation in Russia, this problem has not been systematically studied in large cohorts of patients.The objective was to evaluate the prevalence and severity of renal dysfunction before liver transplantation (LT), during the first postoperative week, at discharge, and one year after surgery.Material and methods. A single-center registry study included data on 550 LTs from living (73%) and deceased (27%) donors performed consecutively between May 2010 and July 2024. Estimated Glomerular filtration rate (eGFR) was calculated using the 2021 CKD-EPI Creatinine formula. Acute kidney injury (AKI) was diagnosed and staged according to RIFLE criteria between 12 hours and day 7 after LT.Results. The median eGFR before LT (n=550), at discharge (n=472) and one year after surgery (n=257) were 107 (86;119), 103 (75;116) and 79 (62;100) mL/min/1.73 m2, and the proportions of patients with eGFR < 60 mL/min/1.73 m2 were 7.1%, 12.7%, and 22.2%, respectively. AKI complicated 33.0% of LTs, including 16.6% cases with RIFLE > I. Renal replacement therapy was used in 7.3% recipients. For the combination of AKI RIFLE > I and early allograft dysfunction (EAD), the 30-day graft survival was 26%, 95%CI: [14–39%].Recipient age (Hazard ratio (HR) 1.07, p<0.001), arterial hypertension (HR 2.2, p=0.010), eGFR at discharge < 60 mL/min/1.73 m2 and tacrolimus trough level (HR 1.18, p<0.001) were independent risk factors for eGFR < 60 mL/min/1.73 m2 one year after LT. The medians of eGFR decline during the first year after LT in cases of de novo administration or conversion to everolimus-based regimens were 11 and 23 mL/min/1.73 m2 (p=0.115) and were not significantly different from the median eGFR decline among recipients never receiving everolimus: p=0.485 and p=0.132, respectively. Five-year survival of recipients with eGFR < 60 mL/min/1.73 m2 at one year after LT was 89.0%, while for eGFR > 60 ml/min/1.73 m2, it was 88.7%, p=0.760.Conclusions. Renal function assessment should be an obligatory part of the follow-up of patients on the waiting list and after LT. Particular attention should be paid to elderly patients, with arterial hypertension, reduced baseline eGFR, post-LT AKI RIFLE > I (especially in combination with EAD). Irrespective of the time after LT, excessive exposure to calcineurin inhibitors (tacrolimus trough level > 10 ng/mL) should be avoided, using combinations with mycophenolates or everolimus if necessary.